Poblamiento y desarrollo cultural en la cuenca de Vera durante la prehistoria reclente. - Delibes de Castro, Germán; Díaz Andreu, Margarita; Martín, Concepción; Montero, Ignacio (Complutum, 1996)
Sin resumen